Discrete Fractional‐Order BAM Neural Networks with Leakage Delay: Existence and Stability Results. Issue 1 (15th October 2018) - Alzabut, Jehad; Tyagi, Swati; Abbas, Syed
Abstract: In this paper, a discrete model of fractional‐order bidirectional associative memory (BAM) neural networks with leakage delay is considered. Sufficient conditions are established for the existence, uniqueness and uniform stability of nontrivial solutions of the addressed model. Our approach is based on the implementation of the newly defined discrete fractional calculus, mathematical inequalities and fixed point theorems. We provide an example that supports the application of the theoretical results.